The customers’ acceptance of Ar-Rahnu scheme: A case study among customer of Bank Rakyat Muar, Johor / Nursyahira Mohd Noh - Mohd Noh, Nursyahira (2016)
The presence of Islamic mortgage scheme (Ar-Rahnu) in Malaysia has captured the hearts of people as one of the new micro instrument of the Islamic financial system. Ar-Rahnu provides facilities of quick cash loans, transparent, fair and based on the principles of Shariah. This research is to study about the customers’ acceptance towards Ar-Rahnu scheme at Bank Rakyat Muar that the factor will be pricing system, shariah view, customer service and advertisement. Due to the problem, there are certain reasons why the research objective was developed. The objective of the study is to determine whether the pricing system, shariah view, customer service and advertisement contribute to the acceptance of the Ar-Rahnu scheme and which factors is the most significant to the customers’ acceptance of Ar-Rahnu scheme.The study employed with a quantitative type of data by using questionnaire and the sample of 291 respondents. The result obtained from this study, found that the most significant factor towards customer acceptance of Ar-Rahnu scheme is customer services followed by the advertisement and Shariah view and there is no relationship between customers’ acceptance and the pricing system